Interfacial Engineering of P3HT/ZnO Hybrid Solar Cells Using Phthalocyanines: A Joint Theoretical and Experimental Investigation. Issue 12 (22nd April 2014) - Mattioli, Giuseppe; Dkhil, Sadok Ben; Saba, Maria Ilenia; Malloci, Giuliano; Melis, Claudio; Alippi, Paola; Filippone, Francesco; Giannozzi, Paolo; Thakur, Anil Kumar; Gaceur, Meriem; Margeat, Olivier; Diallo, Abdou Karim; et al.
<x xml:space="preserve">Abstract</x> Atomistic simulations and experimental investigations are combined to study heterojunction interfaces of hybrid polymer solar cells, with the aim to better understand and precisely predict their photovoltaic properties. The focus is on a hybrid ternary model system based on a poly(3‐hexylthiophene) (P3HT)/zinc phthalocyanine (ZnPc)/ZnO interface, in which a ZnPc interlayer is applied to improve the performance of the hybrid interface. Theoretical predictions of the ternary system are validated against the properties of a concrete P3HT/ZnPc/ZnO planar heterojunction device. The theoretical predictions closely agree with the photovoltaic properties obtained in P3HT/ZnPc/ZnO solar cells, indicating the strength of the method for modeling hybrid heterojunction interfaces. The theoretical and experimental results reveal that: i) ZnPc molecules in direct contact with a ZnO surface insert new energy levels due to a strong ZnPc/ZnO coupling, ii) electron injection from these new energy levels of ZnPc into ZnO is highly efficient, iii) the ZnPc/ZnO coupling strongly influences the energy levels of the ZnO and P3HT leading to a reduction of the open circuit voltage, and iv) charge carrier recombination at the P3HT/ZnO interface is reduced by the ZnPc interlayer. The intercalation of ZnPc leads to an increase in photocurrent as well as to an overall increase in power conversion.